2001
DOI: 10.1046/j.1471-4159.2001.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

The solubility of α‐synuclein in multiple system atrophy differs from that of dementia with Lewy bodies and Parkinson's disease

Abstract: Intracellular inclusions containing a-synuclein (aSN) are pathognomonic features of several neurodegenerative disorders. Inclusions occur in oligodendrocytes in multiple system atrophy (MSA) and in neurons in dementia with Lewy bodies (DLB) and Parkinson's disease (PD). In order to identify disease-associated changes of aSN, this study compared the levels, solubility and molecular weight species of aSN in brain homogenates from MSA, DLB, PD and normal aged controls. In DLB and PD, substantial amounts of deterg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
114
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(127 citation statements)
references
References 36 publications
12
114
0
1
Order By: Relevance
“…As the concentration of monomeric α-syn increases, such that the molar ratio of monomeric α-syn:Hsp27 exceeds 1:1, aggregation occurs. This finding is significant given the association of early onset PD with duplication or triplication of the SNCA gene (56)(57)(58)(59)(60). In these cases, increases in the concentration of α-syn may allow aggregation-prone forms of α-syn to escape the protective capacity of the sHsps.…”
Section: Discussionmentioning
confidence: 99%
“…As the concentration of monomeric α-syn increases, such that the molar ratio of monomeric α-syn:Hsp27 exceeds 1:1, aggregation occurs. This finding is significant given the association of early onset PD with duplication or triplication of the SNCA gene (56)(57)(58)(59)(60). In these cases, increases in the concentration of α-syn may allow aggregation-prone forms of α-syn to escape the protective capacity of the sHsps.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, C-terminal truncation elicits the production of toxic α-syn aggregates and promotes neurodegeneration (10-14, 34, 38-47). Some studies have shown that C-terminally truncated α-syn is found in GCIs in MSA (48,49) as well as in Lewy bodies of PD and DLB patient brains (11,12,39,50,51). Several proteases such as calpain, matrix metalloproteases (MMPs), cathepsin D, and plasmin have been implicated in α-syn truncation, subsequently resulting in increased levels of protein aggregates; however, none has been established as a major producer of C-terminally truncated α-syn in vivo, especially in response to inflammation (12,39,42,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…The facts that the presence of C-terminally truncated ␣-synuclein in LB of sporadic PD and LB dementia (9,10), the existence of various lengths of the truncated forms of ␣-synuclein in brain (10,11), and the formation of C-terminally truncated ␣-synuclein in A53T transgenic mice that show motor symptoms (12) implicate the probable involvement of endopeptidases in cleaving ␣-synuclein in brains. In addition, about 15% of ␣-synuclein in LB are truncated forms, and incomplete degradation of ␣-synuclein produced highly amyloidogenic fragments (9,13). Recent reports showed that matrix metalloproteinases were able to cleave ␣-synuclein, and MMP3 was the most efficient enzyme among them in cleaving ␣-synuclein into several fragments (14).…”
mentioning
confidence: 99%